2022
DOI: 10.4103/jpbs.jpbs_779_21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Zirconia to Dentin Bonding Using Resin-Based Luting Cements and Resin-Modified Glass-Ionomer Cement

Abstract: Introduction: The aim of this study was to compare the shear bond strengths of zirconia to dentin using two resin-based luting cements and a resin-modified glass-ionomer cement (RMGIC). Materials and Methods: Thirty six zirconia blocks of 2 mm × 3 mm × 5 mm were milled and luted to the exposed dentin surfaces and grouped into three according to the cement used for luting: Group I – luted with Panavia F2.0, Group II – luted with RelyX U200, and Group III – luted with Fuj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(32 reference statements)
0
1
1
Order By: Relevance
“…When it comes to the most commonly used cements, decementation was more commonly seen among prostheses cemented with adhesive resin than with glass ionomer in the MZ group. This goes against the results of an in vitro study, in which it was observed that adhesive resin cements present higher bond strength than glass ionomer cements in the bonding between zirconia and dentin [ 103 ]. However, a study observed no difference in the clinical performance for the cementation of zirconia copings between these two types of cement after 48 months [ 104 ].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…When it comes to the most commonly used cements, decementation was more commonly seen among prostheses cemented with adhesive resin than with glass ionomer in the MZ group. This goes against the results of an in vitro study, in which it was observed that adhesive resin cements present higher bond strength than glass ionomer cements in the bonding between zirconia and dentin [ 103 ]. However, a study observed no difference in the clinical performance for the cementation of zirconia copings between these two types of cement after 48 months [ 104 ].…”
Section: Discussioncontrasting
confidence: 59%
“…Moreover, similar clinical outcomes for the cementation of zirconia restorations between these cements were observed in a clinical study [ 112 ].. However, there is no clear consensus on the subject, as other in vitro studies showed that resin-modified glass ionomer cements present lower mean bond strengths between zirconia and dentin than resin-based luting cements [ 103 , 113 ]. The results were not favorable for the conventional glass ionomer cement though.…”
Section: Discussionmentioning
confidence: 61%
“…Consequently, achieving zirconia restorations with high bond strength can be particularly challenging owing to their weaker bond interface with tooth substrates. However, studies have shown improvements in bond strength through surface modifications of zirconia when adhesive cements are employed [10,32].…”
Section: Discussionmentioning
confidence: 99%
“…Its mechanical properties are comparable to those of metals, but the naturality of color increases its election [9]. Y-TZP crowns can be cemented by conventional or resin cements, and the latter reports the highest bond strength values to teeth structures [8,10]; however, the authors reported a high level of debonding of Y-TZP crowns [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%